Studies on MCM-41 air-to-air heat exchanger : fabrication, performance and modeling - Egowibawa, Drajat (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
The present work describes a study on one variation of air-to-air heat exchanger using a novel hydrophilic membrane, i.e. synthesized from MCM-41 inorganic material, to transfer moisture and heat across the membrane. MCM-41 is a mesoporous molecular sieve material. The MCM-41 membrane is synthesized from sol-gel technique at room temperature and developed using deep coating technique with matrix support of polyester mesh. The synthesized MCM-41 material possessed the following properties: BJH pore size of 2.8 nm, wall thickness of 1.12 nm, BET surface area of 1102 m2.g-1, pore volume of 0.97 cm3.g-1 and permeability of 3.622x10-22 m2. A twochamber, concurrent (parallel) flow heat exchanger core is constructed from poly (methyl methacrylate) with the MCM-41 membrane placed in between the chambers. The channel possessed an opening size of 5 mm x 5 mm with total length of 225 mm. The air heat exchanger is intended to operate using outdoor air supply. Thus, two cooling conditions of outdoor air supply are studied; (i) dry air supply as in the case of normal bright day, and (ii) moist air supply as in the case on rainy day. The heat load in the experiment is a hot dry air flow (85 °C and 3%RH). The cooling flow is normal, ambient cooling air fixed at 26 °C and 50%RH. Under the humid or moist air cooling condition, the heat exchanger coefficient is higher i.e. 238.26 W/m2°C as compared to 186.45 W/m2°C obtained under the dry air cooling condition. The improvement in the heat exchanger coefficient is attributed to the increment of the total specific heat capacity in cool flow due to the presence of water droplets in humid cooling flow. Using the finite volume method, the heat exchanger is modeled as three volumes of fluid i.e. the heat load volume, the cooling volume and separated by the MCM-41 membrane volume. All the three volumes are defined as the same fluid but with the membrane volume subjected to porous medium type. Further, the moist cool flow volume is treated as a 3-phase flow volume i.e. air, water vapor and water droplets. The results of the CFD simulation are in very good agreement with the experimental data. The membrane air exchanger model is then further developed to simulate the form of cross-flow heat exchanger. Finally, LBM is used to model the MCM-41 membrane at mesoscale. The model could be used to estimate the permeability of the membrane separator and also to simulate the stream flow profile of fluid upon entering the hive structure of MCM-41.